2005
DOI: 10.1016/j.acra.2005.08.009
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Black-Blood MRI of the Carotid Vessel Wall Using Phased-Array Coils at 1.5 and 3 Tesla1

Abstract: Purpose-To investigate the magnetic field dependence of the signal-to-noise ratio (SNR) for carotid vessel wall magnetic resonance imaging (MRI) using phased-array (PA) surface coils by comparing images obtained at 1.5 T and 3 T, and to determine to what extent the improved SNR at the higher field can be traded for improved spatial resolution.Materials and methods-Two pairs of dual-element PA coils were constructed for operation at the two field strengths. The individual elements of each PA were matched to 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 18 publications
(21 reference statements)
0
26
1
Order By: Relevance
“…The field strength at which images are acquired is another factor that can influence the precision of the measurements. In a recent study (35) a considerable increase in SNR was observed when the field strength was increased from 1.5T to 3T. This increase could be traded for a better in-plane resolution, which in turn could improve the accuracy of the measurements.…”
Section: Discussionmentioning
confidence: 98%
“…The field strength at which images are acquired is another factor that can influence the precision of the measurements. In a recent study (35) a considerable increase in SNR was observed when the field strength was increased from 1.5T to 3T. This increase could be traded for a better in-plane resolution, which in turn could improve the accuracy of the measurements.…”
Section: Discussionmentioning
confidence: 98%
“…The improvement factor was somewhat higher for the four-channel carotid array, at 2.47 for the multiple-image method and 2.39 for the noise-only method. This has been seen by other groups [11] and is related to the small coil area, which leads to a higher proportion of the noise arising from the coil element itself, rather than from the imaging volume. It is higher than seen in vivo in part because of the correction for the relaxation time of the phantom, which was not applied in vivo, but also because of the lower conductivity of the phantom as compared with tissue.…”
Section: Phantom Studymentioning
confidence: 84%
“…One of the early studies, in 2005, used a double inversion recovery (DIR) prepared turbo spin echo (TSE) sequence to image a phantom and healthy volunteers [11]. The phantom experiments demonstrated an SNR increase of a factor of 2.5 for 3 T over 1.5 T, compared with 2.1 in vivo.…”
mentioning
confidence: 99%
“…Imaging of the carotid artery with black-blood MRI can be used to identify plaques that are vulnerable for rupture [1,2]. 3D imaging is particularly interesting to overcome the SNR and volumetric coverage limitations of 2D multislice techniques.…”
Section: Introductionmentioning
confidence: 99%